The intergenerational transmission of opioid dependence - Ahammer, Alexander,Halla, Martin (Johannes Kepler University, Department of Economics, Austria, 2020)
To address the opioid crisis, it is crucial to understand its origins. We provide evidence for the intergenerational transmission of opioid dependence. Our analysis is based on administrative data covering the universe of Austrian births from 1984 to 1990. We consider prescription opioids and have a close proxy for addiction to illicit opioids. We find that, if at least one parent is using illicit opioids, the likelihood of the child using increases from 1.1 to 6.1%. For prescription opioids, we observe an increase from 4.6 to 7.7%. Both associations are stable and do not change when controlling for environmental variables.
10419/220337
Keywords: Graue Literatur; Opioids; prescription opioids; illicit opioids; heroin; addiction; drug abuse; intergenerational transmission; intergenerational correlation